Removal of Tannic Acid from Aqueous Waste Over NaOH Treated Power Plant Fly-Ash - Dakshene, Monika; Jain, Renuka (Asian Journal of Chemistry, 2010)
Waste water containing tannic acid pose grave problems to the environment. As organic molecules are recalcitrant to bio degradation and difficult to treat by conventional methods, their effective removal from pollution generating sites is essential to prevent environmental hazards. In this study, fly ash from coal burning power plant was activated chemically and used as a low cost adsorbent for the removal of tannic acid from their aqueous waste. The activated fly ash was characterized for mineralogical, physiochemical and morphological properties by XRD, FT-IR and SEM analysis. Results showed that activated fly ash due to increased amorphous property possesses more activity over surface to act as a suitable adsorbent for the removal of acidic waste from industrial effluents.